Emmy Schlossberg: capstone - Schlossberg, Emmy, artist (Colorado State University. Libraries, 2025)
The artist's statement: As a graphic designer, I strive to make art that showcases stories and high technical skills. For me, graphic design is all about solving problems. Not only do I make my designs visually appealing, but I also use them as solutions. Moving forward, my design goals are to be able to apply strategic thinking to my designs making sure that every element serves a purpose. Throughout my design thinking process, I like to draw inspiration from the world around me and how music makes me feel. When I'm working on my designs, I listen to a specific genre of music that influences me to make design choices. I show this in many of my designs such as logo and branding design, packaging and print design. From picking out an artistic style to selecting a color palette, each step I take reflects the purpose of the art I design. Each element has a specific meaning to the whole design and this is what makes my designs strong.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design